Nitrogen fixation rates and aerial root production among maize landraces - Connolly, Layne N.; Lorenz, Nicola; Maleki, Keyvan; Kayafas, Noah; Dick, Richard P.; Mercer, Kristin L. (Frontiers in Plant Science, 2025)
In Mexico, the center of maize origin (Zea mays ssp. mays), there are landraces from the highlands that develop extensive aerial root systems which secrete a carbohydrate-rich mucilage. This mucilage produces a favorable environment for nitrogenase activity by diazotrophs. This plant-microbial interaction enables the fixation of nitrogen (N) from the atmosphere, reducing the required N that otherwise must come from the soil and/or fertilizers. The objective of this research was to investigate the degree to which other landraces of maize and nutrient management affect aerial root growth and the ability of maize to perform and benefit from N2 fixation. In two replicated field experiments in Columbus, Ohio, USA in 2019 and 2020, we planted 21 maize landraces and three improved varieties with and without fertilizer to measure their growth, production of aerial roots, and rate of atmospheric N2 fixation using the 15N natural abundance method. Maize accessions varied in the growth rate and number of nodes with aerial roots. Up to 36% of plant N was derived from the atmosphere, with values varying by accession, the reference plant used, and the fertilizer level. Moreover, there was a positive relationship between early growth parameters and numbers of nodes with aerial roots, which, in turn, predicted the amount of N derived from the atmosphere. Thus, larger seedlings may experience enhanced root growth and thereby benefit more from N fixation. By phenotyping a diverse set of maize accessions with and without fertilizer, this study explores both environmental and quantitative genetic variation in the traits involved in N fixation capacity, clarifying that N fixation found in the Sierra Mixe landrace is more broadly distributed than previously thought. In sum, farmers stewarding genetic diversity in a crop center of origin have preserved traits essential for biological symbioses that contribute to maize's nutrient requirements. These traits may enable maize crops grown by Mexican farmers, and farmers globally, to benefit from N fixation from the atmosphere.